Solar Thermal Heating Acceptance Among Malaysian Industries Using System Dynamics - Anis Sabirin Baharom; Nofri Yenita Dahlan (Institute of Advanced Engineering and Science, 2017)
A solar thermal heating technology has a great potential in industries application. This paper presents a prediction of Malaysian industries acceptance on the solar thermal heating system for replacing the current heating technologies. In Malaysia, most of the heating technologies are using fossil fuel as a heating source due to the low price of the source. The solar thermal is another type of sustainable renewable energy. The objective of this research is to produce a Malaysian industries acceptance model in order to study the willingness of the Malaysian industries to migrate and use the new renewable energy technologies in their heating process. System dynamic simulation has been used to develop the novel solar thermal heating acceptance model by using the survey data collected from process industries in Malaysia. The focus of the research is in low and medium temperature categories of the solar thermal system since most of the process industries in Malaysia are involving with low and medium temperature in the heating process. The System Dynamic model was designed to predict the investment decision taken by the industries based on investment decision rules. The results with current support from the government show that the Malaysian industries acceptance towards solar thermal heating technologies is low. To enhance the willingness among the industries, a new policy on solar thermal energy application for industries properly need to be tailored.